Hematopoietic Stem Cell Transplantation Cures Therapy-refractory Aspergillosis in Chronic Granulomatous Disease. Issue 7 (July 2021) - Dedieu, Cinzia; Landwehr-Kenzel, Sybille; Thee, Stephanie; Oevermann, Lena; Voigt, Sebastian; Marggraf, Katharina; Schulte, Johannes; Lau, Susanne; Roesler, Joachim; Kuehl, Jörn-Sven; von Bernuth, Horst
Abstract : Background: Pulmonary invasive aspergillosis is a frequent and life-threatening complication for patients with chronic granulomatous disease (CGD). Despite combined treatment with several groups of antifungal agents, conservative treatment of invasive aspergillosis often remains refractory. Pulmonary invasive aspergillosis is often treated by surgical resection of consolidated lobes or segments, donor granulocyte transfusions and allogeneic hematopoietic stem cell transplantation (HSCT). These options are not mutually exclusive and often combined. Methods and Results: We here describe the treatment of 3 patients with CGD who received HSCT upon active pulmonary invasive aspergillosis: Two of them received HSCT as salvage therapy for refractory aspergillosis, and 1 patient received elective HSCT in infancy but developed pulmonary aspergillosis during secondary graft failure. Based on our experience and available literature, we discuss indication as well as timing of HSCT, granulocyte transfusions and surgery in patients with CGD and pulmonary invasive aspergillosis. Conclusions: Upon diagnosis with invasive aspergillosis in CGD, we propose to start antifungal treatment and preparation for HSCT at the same time. Remission of pulmonary invasive aspergillosis before HSCT remains preferable but is not mandatory. When pulmonary aspergillosis in patients with CGD remains refractory for longer than 3 months on conservative treatment, HSCT without prior surgery or accompanying granulocyte transfusions is a feasible option. Abstract : Supplemental Digital Content is available in the text.